Endophytic fungi as regulators of phytohormones production: Cytomolecular effects on plant growth, stress protection and importance in sustainable agriculture - Parissa Taheri (Plant Stress, 2025)
Plants adjust their physiology, biology and phenotype to survive in various environmental situations and organize their responses to unfavorable conditions. Phenotypic and physiologic flexibility of various plant species may be mediated by numerous microorganisms, including endophytic fungi. These beneficial fungi are capable of increasing plant growth via either enhancing plant immunity to biotic and abiotic environmental stimuli, or by producing growth-stimulating factors such as phytohormones. Phytohormones have vital roles in plant resistance mechanisms and can be considered as growth regulators via their prominent effect on plant metabolism. Exogenous use of various hormones can increase plant growth factors and decrease harmful effects of environmental stresses. Recent investigations revealed that phytohormones production or regulation by beneficial fungi could be critical metabolic engineering targets for activating plant resistance to environmental stimuli. Signaling pathways involved in phytohormones biosynthesis and mechanisms related to this process have been identified using numerous biochemical and molecular approaches. This review is focused on production and regulation of some phytohormones by endophytic fungi and current knowledge on the vital role of these small biological molecules in increasing immunity responses in plants exposed to environmental cues. Therefore, the present review can be useful for plant pathologists, physiologists and environmental microbiologists for designing novel and effective strategies to develop broad-spectrum microbial inoculants supporting plant growth and organic crop production under unfavorable conditions. Focus on exploring cytomolecular and biochemical mechanisms involved in the effect of fungi and other beneficial microbes on producing or regulating phytohormone levels in plant tissues seems to be interesting subjects for future research.